Against Revision: Strawson on Analysis and Metaphysics - Torres, David Eduardo (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2025)
This dissertation aims to provide a comprehensive and systematic account of Peter Frederick Strawson's contributions to philosophical methodology, particularly in the realms of analysis and metaphysics. Despite his significant influence since the 1950s, there remains a notable gap in the literature regarding Strawson's metaphilosophical approach, particularly in relation to semantics and the philosophy of language. While there exists one other doctoral thesis that directly addresses Strawson's philosophical method, my work emphasizes how his thoughts on language and semantics inform his broader metaphysical project. The primary objectives of this research include: (1) offering a unified overview of Strawson's views on analysis and metaphysics, highlighting the interconnections between his philosophy of language and his project of descriptive metaphysics; (2) reconstructing Strawson's philosophical method as it pertains to language and ontology; (3) dispelling standing misconceptions surrounding his work; and (4) presenting descriptive metaphysics as a viable and productive avenue for contemporary ontology. The dissertation is structured in two parts. Part 1 includes four chapters that examine analysis through the lens of the philosophy of language. The second part consists of two chapters dealing with analysis in the context of ontology and metaphysics. Chapter 1 reconstructs Strawson's critique of classical and constructivist forms of analysis, countering the notion that he opposed system construction. Chapter 2 explores Strawson's prospects for a logic for ordinary language, refuting claims that he dismissed the possibility of a systematic theory of meaning. Chapter 3 elaborates on the prior chapter by delving into Strawson's criteria for a semantic theory and the aim of a perspicuous grammar. Chapter 4 focuses on his conception of semantic content, portraying him as a proto-contextualist and debunking the accusation of conflation between semantics and pragmatics. Chapter 5 examines Strawson's view on the semantics of proper names, challenging the accusation that he adhered to traditional descriptivism. Chapter 6 discusses his method of descriptive metaphysics, arguing against the idea that it solely addresses our conceptual scheme without offering insights into the nature of reality. Chapter 7 synthesizes the prior material and argues against radical conceptual revision, setting the boundaries of conceptual engineering and positioning descriptive metaphysics as an essential framework for any revisionary proposals. Overall, a central conviction underpinning this research is that neglecting the deep interconnections within Strawson's work across various subjects results in an incomplete understanding of his philosophy. This oversight obscures critical elements essential for grasping the aims of his general project of philosophical elucidation. By highlighting the fundamental coherence of his work, I aim to provide an interpretation that accurately reflects and clarifies Strawson's doctrine, ultimately restoring its essential sharpness and undeniable ingenuity.
APPROVED
Keywords: Metaphysics; Analysis; Strawson; Descriptive Metaphysics; Conceptual Analysis; Philosophical Methodology; Metametaphysics; Semantics